2014
DOI: 10.3892/ijo.2014.2669
|View full text |Cite
|
Sign up to set email alerts
|

p62/SQSTM1 is involved in cisplatin resistance in human ovarian cancer cells via the Keap1-Nrf2-ARE system

Abstract: The mechanisms underlying cisplatin resistance in tumors are not fully understood. Previous studies have reported that cellular resistance to oxidative stress is accompanied by resistance to cisplatin. However, the relationship between the resistance to oxidative stress and cisplatin drug resistance in human ovarian cancer cells (HOCCs) is not clear. Here, we reveal a critical role for the multifunctional protein p62/SQSTM1 in cisplatin resistance in human ovarian cancer cells (HOCCs). p62/SQSTM1 (sequestosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 27 publications
3
46
0
Order By: Relevance
“…Second, p62 gene contain an ARE (antioxidant response element) in its promoter, which is a specific Nrf2‐binding site by which Nrf2 induces p62 transcription . Moreover, Nrf2 and p62 were upregulated in some cancers such as liver cancer , gliomas , ovarian cancer , and breast cancer . In this study, we confirmed that Nrf2 and p62 were overexpressed and there was a positive correlation between them in breast cancer tissues and cells.…”
Section: Discussionsupporting
confidence: 71%
“…Second, p62 gene contain an ARE (antioxidant response element) in its promoter, which is a specific Nrf2‐binding site by which Nrf2 induces p62 transcription . Moreover, Nrf2 and p62 were upregulated in some cancers such as liver cancer , gliomas , ovarian cancer , and breast cancer . In this study, we confirmed that Nrf2 and p62 were overexpressed and there was a positive correlation between them in breast cancer tissues and cells.…”
Section: Discussionsupporting
confidence: 71%
“…The poor outcome associated with high p62 level may be also explained by a pro-survival NF-κB-dependent mechanism that could synergize with autophagy to promote tumor growth 20 . In addition, p62 could activate a protective antioxidant response by engaging the Keap1-Nrf2 signaling pathway and delivers resistance to chemotherapy 45 . Thus, the efficacy of co-targeting p62 in a cetuximab-based regimen warrants future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 However, recent studies showed that cisplatinresistant ovarian cancer cells express much higher levels of SQSTM1 than do cisplatin-sensitive ovarian cancer cells. 38,39 In addition, the level of SQSTM1 was increased in osteosarcoma cell lines after cisplatin treatment following a temporary decrease at the onset of treatment. 40 Consistent with these studies, the level of SQSTM1 was increased in cisplatin-treated MG-63 cells (Fig.…”
Section: Gfra1 Regulates Autophagy Through Src-ampk Signalingmentioning
confidence: 99%